THE EFFECTIVENESS OF USING MIND MAPPING TECHNIQUE IN TEACHING RECOUNT TEXT TO INCREASE THE STUDENTS’ WRITING ABILITY : THE EFFECTIVENESS OF USING MIND MAPPING TECHNIQUE IN TEACHING RECOUNT TEXT TO INCREASE THE STUDENTS’ WRITING ABILITY - Yahrif, Muhammad (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MEGAREZKY, 2021)
The objective of this study is to find out the effectiveness of using the mind mapping technique in teaching recount text to increase the students’ writing ability. This research is quasi-experimental as the design that used two group pretest and posttest. It means that there were an experimental class and a controlled class which were given pretest and posttest. There were 37 students of class X of SMAN 12 Makassar as the sample in this study. The instrument of this research was a written test, to score the students’ recount text on pretest and posttest. The result of this research showed that there was a positive effect of the result of students' recount text after using the mind mapping technique. Based on the result of the calculation process the researcher gained that in pretest had a mean of 61,24 and the posttest had a mean of 81.03 of experimental class. Based on the finding of this study, it can be concluded that using mind mapping in teaching recount text is quite a success. And after conducting the research and calculating the data, It could be stated that it was effective of using mind mapping on students' writing of recount text. Students' writing of recount text got a higher score.